Analisis Pengaruh Citra Perusahaan dan Kepuasan Pelanggan Terhadap Loyalitas Merek: Studi pada Konsumen Toko Retail Superindo Semarang - Katarina Ayudya Kanda; Ardiaz Ajie Aryandika (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to analyze the effect of corporate image on brand loyalty with customer satisfaction as an intervening variable among Superindo customers in Semarang City. This study is motivated by the increasingly fierce competition in the modern retail industry in Indonesia, which requires companies to not only offer quality products, but also build a positive corporate image and create customer satisfaction in order to maintain long-term brand loyalty. This study uses a quantitative approach with data collection methods through the distribution of questionnaires to Superindo customers in Semarang City. The sample size in this study was 100 respondents selected using purposive sampling techniques. Data analysis was performed using the Structural Equation Modelling (SEM) method with a Partial Least Square (PLS) approach using SmartPLS software. The results of the study indicate that corporate image has a positive and significant effect on customer satisfaction and brand loyalty. In addition, customer satisfaction also has a positive and significant effect on brand loyalty. Customer satisfaction has been proven to mediate the effect of corporate image on brand loyalty, which shows that a good corporate image can increase customer satisfaction and ultimately encourage the formation of brand loyalty among Superindo customers. The findings of this study have important implications for Superindo's management in formulating marketing and service strategies, particularly in efforts to strengthen the company's image through improving service quality, shopping convenience, and employee interaction with customers. In addition, the company needs to consistently maintain customer satisfaction as a key factor in building and maintaining brand loyalty amid increasingly competitive modern retail competition.